Vertical spectra consistent with horizontal seismic hazard. Issue 157 (June 2022) - Sriwastav, Ravi Kanth; Basu, Dhiman
Abstract: Construction of vertical spectra (V) for scenario- and intensity-based seismic performance assessment is proposed based on scaling of the associated horizontal spectral ordinates (H) through respective V/H spectral ratios. Geometric mean of the spectra along and normal to the principal plane components is considered as the intensity measure of the horizontal component. V/H spectral shape is constructed using a large database (PEER-NGA-WEST2) of strong motion records contingent on the magnitude of the event, epicentral distance and average shear wave velocity. The procedure is based on the ratio of median vertical-to median horizontal-spectral ordinates which are shown to be well representative of the median of V/H spectral ratio. The construction is based on median response of the scenario and also applies to the design level (of a particular facility located in a specific site, which is also governed by a scenario) under certain assumptions and involves two steps: construction of normalized V/H spectra with unity at zero period scaled by the ratio of median vertical-to median horizontal- PGA ( beta ). The normalized V/H spectrum is shown to be characterized by three control points. An empirical estimate is proposed for beta as a function of epicentral distance. Normalized V/H spectra are further idealized for use with the intensity-based assessment per seismic codes. Vertical spectra using the proposed framework are compared with the various recommendations reported in the prior art including seismic codes and recorded events. PESMOS and COSMOS databases of strong motion events recorded in the Indian subcontinent are also used during the assessment. Highlights: Vertical spectra for scenario- and intensity- based assessment is proposed. Recommendation for V/H spectral shape. Prediction for ratio of vertical-to horizontal peak ground acceleration. Comparison with GMPM of V/H. Assessment against recorded ground motion.